Влияние термомеханической обработки на структуру и свойства сплава Al-Mg-Si - Березина, А.Л.; Монастырская, Т.А.; Давиденко, А.А.; Спусканюк, В.З.; Гангало, А.Н.; Котко, А.В. (Физика и техника высоких давлений, 2012)
Исследована возможность изменения структуры и свойств деформируемого малолегированного дешевого сплава АД-31 за счет применения различных схем интенсивной пластической деформации (ИПД) в сочетании с термообработками разного типа. Показано, что использование ИПД при комнатной температуре для сплава АД-31 формирует неоднородную деформационную структуру, которая представляет собой картину незавершенной динамической рекристаллизации. Средний размер зерен уменьшается от 200−500 μm до 300–500 nm. ИПД, независимо от исходных состояний сплава, способствует деформационно-индуцированному полному или частичному растворению избыточных фаз, что сопровождается образованием пересыщенного твердого раствора в матрице. За счет измельчения зерен и образования субструктуры в предварительно состаренных образцах удается повысить предел прочности по сравнению с исходным состаренным состоянием от 200 до 390 MPa при снижении относительного удлинения на 30%. Досліджено можливість зміни структури й властивостей дешевого малолегованого сплаву АД-31, що деформується, за рахунок застосування різних схем інтенсивної пластичної деформації (ІПД) у поєднанні з різного типу термообробками. Показано, що використання ІПД при кімнатній температурі для сплаву АД-31 формує неоднорідну деформаційну структуру, яка являє собою картину незавершеної динамічної рекристалізації. Середній розмір зерен зменшується від 200–500 μm до 300–500 nm. ІПД, незалежно від вихідних станів сплаву, сприяє деформаційноіндукованому повному або частковому розчиненню надлишкових фаз, що супроводжується утворенням пересиченого твердого розчину в матриці. За рахунок подрібнення зерна й утворення субструктури в попередньо зістарених зразках вдається підвищити межу міцності порівняно з вихідним зістареним станом від 200 до 390 MPa при зниженні відносного видовження на 30%. Now it is supposed that the mechanism of hardening of pure metals resulting from severe plastic deformation (SPD) is based on the refinement of grains and the nonequilibrium state of grain boundaries with a high level of local internal stresses near the boundaries. However, in some heterogeneous alloys, not only grain refinement during SPD, but also formation or dissolution of secondary dispersed phases also affects mechanical properties. The effect of additional hardening or softening is observed, depending on the structural state of these phases in a wide range of deformation. Such effects were found in aging aluminium alloys after three-dimensional SPD. Formation of a SMC structure in relatively inexpensive industrial aluminum alloys due to the use of these technologies can transform low-strength alloys into mediumstrength and high-strength ones. Aging aluminium alloys with SMC structures can be used for producing heavy-duty castings with high performance. The possibility of modification of the structure and the properties of the wrought lowalloyed, low-cost Al−Mg−Si alloy of 6060 type by the use of SPD has been studied. The alloy has high plasticity, the ability for hot extrusion, and high corrosion resistance, which are excellent characteristics for various applications. Low strength of the alloy, however, is the main disadvantage. The search for additional methods of hardening of the alloy is of great interest. The primary task of this research was studying of the possibility of improving the mechanical properties of the alloy with using various modes of severe plastic deformation combined with different types of thermal treatment before and after SPD. It was shown that the use of SPD at room temperature for Al−Mg−Si alloy formed a heterogeneous deformation structure which is characterized by incomplete dynamic recrystallization. The average grain size decreased from 200−500 μm to 300−500 nm. SPD provoked the deformation-induced complete or partial dissolution of excess phases, regardless of the initial state of the alloy. This process was accompanied by the formation of a supersaturated solid solution in the matrix. Grain refinement and substructure formation led to the increase in the ultimate tensile strength from 200 to 390 MPa in the preaged samples, their elongation being reduced by 30%.